Microleakage of CEM Cement and ProRoot MTA as Furcal Perforation Repair Materials in Primary Teeth - Haghgoo, Roza; Arfa, Sara; Asgary, Saeed (Iranian Endodontic Journal, 2013)
Introduction: Iatrogenic furcal perforation is a procedural accident in endodontic treatments of primary/permanent teeth; prognosis may be favorable if a complete seal with biomaterial is immediately established. The purpose of this in vitro study was to evaluate microleakage of calcium enriched mixture (CEM) cement and ProRoot mineral trioxide aggregate (MTA) for sealing primary molar furcal perforations. Materials and Methods: This study was conducted on 38 extracted human primary molars. Furcation perforations were created in the pulp chamber floor. The teeth were divided randomly in two experimental groups (n=17) and two positive and negative controls (n=2). Perforations were then repaired with biomaterials. After 72 h, the teeth were submerged in 2% fuchsin dye solution for 24h. The samples were sectioned longitudinally and evaluated for dye leakage. Data analyzed statistically using ANOVA test. Results: The negative and positive controls behaved as expected. Dye microleakage was observed in all experimental samples; however, there was no statistically significant difference between the microleakage of MTA (4.411±2.042 mm) and CEM (3.647±1.040 mm) groups (P>0.05). Conclusion: Based on the findings of this in vitro study, CEM and tooth-colored ProRoot MTA have similar sealing ability for furcal perforation repair of primary molar teeth.